Standarisasi Mutu Pembelajaran: Studi di IAIN Surakarta dan Kasem Bundit University Thailand - Makruf, Imam (SHAHIH : Journal of Islamicate Multidisciplinary, 2016)
AbstractObvious learning quality standardization is necessary in order to raise the quality of the Institute, starting from lesson plan, learning process, until its evaluation. This article is going to investigate the comparison of learning quality standard between IAIN Surakarta and Kasem Bundit University. In the implementation, whether IAIN Surakarta and Kasem Bundit University have formulas related to the learning quality standard starting from lesson plan, learning process, until its evaluation. However, there is a big difference in the available documents. In IAIN Surakarta the documents are more administrative in purpose since it is in the form of procedure guidelines and have not completed yet. While the documents in Kasem Bundit University are more quality manual in purpose which formulate various learning quality standard of many components, indicators, and its indicator descriptions. Keywords: Learning quality standard, plan, implementation, evaluation AbstrakUntuk mengangkat mutu lembaga dibutuhkan standarisasi mutu yang jelas mulai dari perencanaan, pelaksanaan, sampai dengan evaluasi pembelajarannya. Artikel ini mengkaji perbandingan standar mutu pembelajaran di IAIN Surakarta dan Kasem Bundit University. Dalam pelaksanaannya baik di IAIN Surakarta maupun di Kasem Bundit University memiliki rumusan-rumusan terkait standarisasi mutu pembelajaran mulai dari perencanaan, pelaksanaan, maupun evaluasinya. Namun demikian terdapat perbedaan yang cukup besar, yaitu di IAIN Surakarta dokumen yang sudah tersedia lebih bersifat administratif karena berupa pedoman prosedur dan itupun belum lengkap. Sementara itu di Kasem Bundit University dokumen yang ada lebih bersifat manual mutu yang merumuskan berbagai standar mutu pembelajaran dalam berbagai komponen, indikator, dan deskripsi indikatornya. Kata Kunci: standar mutu pembelajaran, perencanaan, pelaksanaan, evaluasi